Moderate ethanol exposure during early ontogeny of the rat alters respiratory plasticity, ultrasonic distress vocalizations, increases brain catalase activity, and acetaldehyde-mediated ethanol intake - D’aloisio, Genesis; Acevedo, María Belén; Angulo-Alcalde, Asier; Trujillo, Verónica; Molina, Juan Carlos (Frontiers in Behavioral Neuroscience, 2022)
Early ontogeny of the rat (late gestation and postnatal first week) is a sensitive period to ethanol's positive reinforcing effects and its detrimental effects on respiratory plasticity. Recent studies show that acetaldehyde, the first ethanol metabolite, plays a key role in the modulation of ethanol motivational effects. Ethanol brain metabolization into acetaldehyde via the catalase system appears critical in modulating ethanol positive reinforcing consequences. Catalase system activity peak levels occur early in the ontogeny. Yet, the role of ethanol-derived acetaldehyde during the late gestational period on respiration response, ultrasonic vocalizations (USVs), and ethanol intake during the first week of the rat remains poorly explored. In the present study, pregnant rats were given a subcutaneous injection of an acetaldehyde-sequestering agent (D-penicillamine, 50 mg/kg) or saline (0.9% NaCl), 30 minutes prior to an intragastric administration of ethanol (2.0 g/kg) or water (vehicle) on gestational days 17-20. Respiration rates (breaths/min) and apneic episodes in a whole-body plethysmograph were registered on postnatal days (PDs) 2 and 4, while simultaneously pups received milk or ethanol infusions for 40-min in an artificial lactation test. Each intake test was followed by a 5-min long USVs emission record. On PD 8, immediately after pups completed a 15-min ethanol intake test, brain samples were collected and kept frozen for catalase activity determination. Results indicated that a moderate experience with ethanol during the late gestational period disrupted breathing plasticity, increased ethanol intake, as well brain catalase activity. Animals postnatally exposed to ethanol increased their ethanol intake and exerted differential affective reactions on USVs and apneic episodes depending on whether the experience with ethanol occur prenatal or postnatally. Under the present experimental conditions, we failed to observe, a clear role of acetaldehyde mediating ethanol’s effects on respiratory plasticity or affective states, nevertheless gestational acetaldehyde was of crucial importance in determining subsequent ethanol intake affinity. As a whole, results emphasize the importance of considering the participation of acetaldehyde in fetal programming processes derived from a brief moderate ethanol experience early in development, which in turn, argues against “safe or harmless” ethanol levels of exposure.